The Entrainment Of Gangue Into A Flotation Froth - S. J. Neethling (Society for Mining, Metallurgy & Exploration, 2001)
The flotation froth structure and motion determines the amount of entrained gangue that is collected to the concentrate. Despite this important role in the overall performance, the behaviour of the froth is still ill understood. To date, predominantly empirical models have been developed to describe entrainment. A fundamentally based model is described and used here in an attempt to improve the understanding of entrainment. This general froth simulator (UMIST FrothSim) allows the modelling of a wide range of flotation conditions, as it takes account of a large number of the physical phenomena that occur within flotation froths. The model firstly describes gas motion and bubble coalescence, and the water motion based on gravitational, viscous and capillary effects. The motion of the solids distinguishes between various solids classes based on hydrophobicity, particle size and density and models them by including the effects of Geometric and Plateau border dispersion, particle settling and the motion of the water. The aim of this paper is to show the applicability of this model to explain the observed entrainment and collection of gangue. This is done by comparing model predictions with the experimentally observed relationship between the gangue and water recoveries. The model predicts the identical trends, which are explained in terms of the interaction between the linear effects of water motion and hindered settling and the non-linear effect of particle dispersion.